2018
DOI: 10.3390/ijms19010212
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Different Platelet Lysates and Platelet Rich Preparations to Stimulate Tendon Cell Biology: An In Vitro Study

Abstract: Abstract:The poor healing potential of tendons is still a clinical problem, and the use of Platelet Rich Plasma (PRP) was hypothesized to stimulate healing. As the efficacy of PRPs remains unproven, platelet lysate (PL) could be an alternative with its main advantages of storage and characterization before use. Five different blood products were prepared from 16 male donors: human serum, two PRPs (Arthrex, (PRP-ACP); RegenLab (PRP-BCT)), platelet concentrate (apheresis, PC), and PL (freezing-thawing destructio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
60
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 70 publications
0
60
0
3
Order By: Relevance
“…These drawbacks can be mitigated by using chair-side hemoderivates such as P-PRP, L-PRP or i-PRF, which are processed chairside in closed systems, thereby reducing the possibility of cross-contamination. Recent attempts to assess the performance of HPL compared to traditional PRP [36] have demonstrated that high concentrations of growth factors, such as TGF-β1, VEGF, PDGF-AB, in platelet lysate, did not result in increased cell viability or extracellular matrix protein gene expression. It was hypothesised that some of the growth factors involved in cell proliferation could be altered or degraded during the freezing step at −80 • C, resulting in a reduced impact on cellular behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…These drawbacks can be mitigated by using chair-side hemoderivates such as P-PRP, L-PRP or i-PRF, which are processed chairside in closed systems, thereby reducing the possibility of cross-contamination. Recent attempts to assess the performance of HPL compared to traditional PRP [36] have demonstrated that high concentrations of growth factors, such as TGF-β1, VEGF, PDGF-AB, in platelet lysate, did not result in increased cell viability or extracellular matrix protein gene expression. It was hypothesised that some of the growth factors involved in cell proliferation could be altered or degraded during the freezing step at −80 • C, resulting in a reduced impact on cellular behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Klatte-Schulz & Schmidt, 2018). Different numbers of freeze/thaw cycles are suggested in available protocols with the preferred cycle number of 3-5(Strandberg et al, 2017).…”
mentioning
confidence: 99%
“…We used the ACD-A tubes to make homemade PRP s after evaluating the various protocols published in the literature [1][2][3][4][5][6][7][8][9][10][11][12]. There are many protocols for PRP and different concentrations are reported while using different spin times and different g forces.…”
Section: Discussionmentioning
confidence: 99%
“…Different PRP volumes can be obtained according to the tubes used. Approximately 1 cc from the tube containing 8.5 cc of blood + 1.5 cc ACDA containing ACDA, about 0.25 cc of PRP from the 2.5 cc volume of Na citrated tube can be obtained [3][4][5][6][7][8][9][10]. In fact, the amount of PRP collected is EXPERIMENTAL BIOMEDICAL RESEARCH http://www.experimentalbiomedicalresearch.com related to how much the amount is concentrated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation